Impact of Corporate Culture on the Universities' Achievements in the "5-100" Project - V. A. Pushnykh; N. S. Gulius; E. Yu. Yatkina (Moscow Polytechnic University, 2021)
The project called "5-100" has been established in Russia in 2013 for the period of time from 2013 up to 2020. It was supposed that this project would be resulted in entry of 5 Russian universities into 100 highest positions of the world university ratings. 21 Russian universities were chosen as the participants of the project. To achieve the purpose of the project, every chosen university received considerable financial support from the Russian federal government. Among others, two universities from the city of Tomsk - Tomsk State University (TSU) and Tomsk Polytechnic University (TPU) were the participants of this project. In spite of the identical starting points, the universities have demonstrated substantially different results by the end of the project implementation. In this article, we attempted to explain the difference of the results through difference of the corporate cultures of both universities. The corporate culture study has been done using OCAI method. The study showed that TGU's corporate culture looks like more competitive than TPU's one. It was proved by the comparison of the TPU and TGU cultures with cultures of the foreign universities.